Development of Polypropylene-Polylactide Blends and their Degradation by Bacterial Isolates - Jain, Kimi (My University, 2017)
Polypropylene (PP) is widely used polymer in packaging applications as it is flexible, economical, resistant to water and water-borne organisms and possesses excellent barrier properties. But it is non-biodegradable in nature and causes environmental pollution as well as also harms the wildlife. Therefore, it is essential to find some ways to biodegrade the polymer. The biodegradation of polypropylene (PP) can be enhanced by using two approaches; one, by blending polypropylene with some biodegradable polymer and secondly, by isolating efficient microorganisms having capability to degrade polypropylene. In our study, both the approaches have been used simultaneously to make polypropylene degradable. Firstly, polypropylene was blended with poly-L-lactide (PLLA) in varying ratios and with/without compatibilizer maleic anhydride grafted polypropylene (MAPP) to develop biodegradable polymers which were optimized on the basis of mechanical properties. Secondly, effect of blend composition and compatibilizer content on the physicochemical properties of blends was investigated via X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning electron microscopy (SEM) and Thermogravimetric analysis (TGA). Thirdly, degradation of selected blends was studied using abiotic and biotic factors. PP/PLLA blends with ratio of 80:20 (without compatibilizer, PP80) and 80:20:6 ratio (with compatibilizer, PP80C6) showed optimum mechanical properties. The results of physicochemical properties revealed that PP80C6 possessed more mechanical strength, better thermal stability, improved interfacial adhesion as compared to PP80 due to interactions formed between PP and PLLA by the addition of MAPP. Therefore, two blends namely PP80 and PP80C6 were selected for further studies. The biodegradation of selected blends was studied by using bacteria isolated from compost. Rationally, sixteen bacteria (P1-P16) were isolated by using enrichment technique. P3, P6, P8, P10 and P13 were selected on the basis of their degradation efficiency and identified as Bacillus sp. The bacterial isolate P8 i.e., Bacillus thuringenesis showed the maximum potential to degrade blends in synthetic media as well as in soil (microcosm) under laboratory conditions. Field study was conducted using consortium made of all the five bacterial isolates. It showed decrease in mechanical strength and thermal stability of blends after degradation for six months. The blends degraded by bacterial isolates in soil according to ASTM D 5338 showed percentage biodegradation of 9-12% and the highest degradation was caused by P8. The results suggest that bacterial isolates have potential to degrade PP/PLLA blends in an efficient manner and P8 showed the largest potential. So, the bacterial isolate P8 can be further studied for enzyme production and genes responsible for it.
Keywords: Polypropylene, biodegradation, polylactide, Bacillus species, bacteria